Building with structural insulated panels (SIPs) : strength and energy efficiency through structural panel construction / Michael Morley. - Morley, Michael (Taunton, 2000)
This work takes the reader through the entire process of building a panel-constructed house - from planning and estimating, ordering, storage and handling to construction